3D PROTOCOLO OF MEDICINAL BIOMAGNETISM THE TREATMENT OF OBESITY - Midding Lazzari, Claudete; Pitondo da Silva Peplinski, Sandra; Mara Rambo, Angela; Maria Oliveira Lima, Márcia; Viapiana Bossa, Adriane (Health and Society, 2023)
Medicinal Biomagnetism (MB), developed by Dr. Isaac Goiz Durán, is a therapeutic technique aimed at diagnosing, treating, and preventing diseases by adjusting the pH of specific body regions. This method utilizes static magnetic fields generated by magnets applied to specific points to regulate biomagnetic fields and treat pathologies. With obesity becoming a globally prevalent dysfunction, safe and effective therapeutic alternatives are necessary. In this descriptive cross-sectional study with a quantitative approach, we assessed the effect of the MB 3D Protocol on an obese patient using bioimpedance. The protocol was applied in 15 sessions over 15 weeks. The results revealed significant improvements in the evaluated measurements, although the body mass index (BMI) did not change categories. It is concluded that the MB 3D Protocol demonstrated promising results in the treatment of obesity, highlighting its relevance as a complementary therapeutic tool. Further studies are necessary to validate these findings and better understand its role in obesity management.